Foraminiferal raw counts, sedimentation rates, total foraminiferal absolute and relative abundance, dominant species percentages, foraminiferal microhabitats, ecological groups, oxygen index, TOC, stable isotope data, C37 alkenones and UP10 data - José N Pérez-Asensio; Jaime Frigola; Leopoldo D Pena; Francisco Javier Sierro; Maria Isabel Reguera; Francisco Javier Rodríguez-Tovar; Javier Dorador; Alessandra Asioli; Jannis Kuhlmann; Katrin Huhn; Isabel Cacho (PANGAEA, 2020)
The accumulation of an Organic Rich Layer (ORL) during the last deglaciation in the Alboran Sea (western Mediterranean Sea) and its link to changes in deep and intermediate water circulation are here investigated. Benthic foraminiferal assemblages and the shallow infaunal foraminifer Uvigerina peregrina δ13C record support the establishment of sustained high organic matter fluxes, and thus eutrophic conditions at the sea floor, during the late phase of the ORL (Younger Dryas to early Holocene periods). Since organic matter fluxes were lower (mesotrophic conditions) during the Bølling-Allerød period, they cannot be solely responsible for the ORL initiation. Geochemical, sedimentological and micropalaeontological proxies support a major weakening of the deep-water convection in the Gulf of Lion as the main driver for the development of poorly-ventilated conditions from intermediate depths (946 m) to the deep western Mediterranean basin that promoted the beginning of the ORL deposition. Nevertheless, a better ventilation at intermediate depths was established during the late ORL, while the deep basin remained poorly ventilated. We propose that our data reflect the arrival of a new better-ventilated intermediate water mass analogue to the current Levantine Intermediate Water (LIW) and/or a new intermediate water mass from the Gulf of Lion. The ultimate source of this water mass needs to be further explored but chronologies of the changes recorded here indicate that intermediate and deep ventilation phases were decoupled between the western and eastern Mediterranean basins during the deglaciation and early-middle Holocene.
Supplement to: Pérez-Asensio, JN et al. (2020): Changes in western Mediterranean thermohaline circulation in association with a deglacial Organic Rich Layer formation in the Alboran Sea. Quaternary Science Reviews, 228, 106075, https://doi.org/10.1016/j.quascirev.2019.106075